A novel fibrinolytic metalloproteinase, barnettlysin-I from Bothrops barnetti (barnett´s pitviper) snake venom with anti-platelet properties - Eladio F. Sánchez; Michael Richardson; Luiza Helena Gremski; Sílvio Sanches Veiga; Armando Yarlequé; Stephan Niland; Augusto Martins Lima; Maria Inácia Estevão-Costa; Johannes A. Eble (2015)
Viperid snake venoms contain active components that interfere with hemostasis. We report a new P-I class snake venom metalloproteinase (SVMP), barnettlysin-I (Bar-I), isolated from the venom of Bothrops barnetti and evaluated its fibrinolytic and antithrombotic potential. Bar-I was purified using a combination of molecular exclusion and cation-exchange chromatographies. We describe some biochemical features of Bar-I associated with its effects on hemostasis and platelet function. Bar-I is a 23.386 kDa single-chain polypeptide with pI of 6.7. Its sequence (202 residues) shows high homology to other members of the SVMPs. The enzymatic activity on dimethylcasein (DMC) is inhibited by metalloproteinase inhibitors e.g. EDTA, and by α2-macroglobulin. Bar-I degrades fibrin and fibrinogen dose- and time-dependently by cleaving their α-chains. Furthermore, it hydrolyses plasma fibronectin but not laminin nor collagen type I. In vitro Bar-I dissolves fibrin clots made either from purified fibrinogen or from whole blood. In contrast to many other P-I SVMPs, Bar-I is devoid of hemorrhagic activity. Also, Bar-I dose- and time-dependently inhibits aggregation of washed human platelets induced by vWF plus ristocetin and collagen (IC50 = 1.3 and 3.2 μM, respectively), presumably Bar-I cleaves both vWF and GPIb. Thus, it effectively inhibits vWF-induced platelet aggregation. Moreover, this proteinase cleaves the collagen-binding α2-A domain (160 kDa) of α2β1-integrin. This explains why it additionally inhibits collagen-induced platelet activation. A non-hemorrhagic but fibrinolytic metalloproteinase dissolves fibrin clots in vitro and impairs platelet function. This study provides new opportunities for drug development of a fibrinolytic agent with antithrombotic effect.